First-Degree Relatives of Patients with Type 2 Diabetes Mellitus and Risk of Non-Alcoholic Fatty Liver Disease - Adibi, Atoosa (SBDR - Society for Biomedical Diabetes Research, 2007)
AIMS: The aim of this study was to determine whether first-degree relatives (FDR) of patients with type 2 diabetes mellitus (T2DM) are at higher risk of non-alcoholic fatty liver disease (NAFLD) than healthy controls. METHODS: A total of 222 FDR of consecutive patients with T2DM aged between 35 and 55 years and 202 healthy individuals with no family history of diabetes were investigated for NAFLD. Fatty liver was diagnosed by ultrasonography using standard criteria. Height, weight, fasting glucose, alanine aminotransferase (ALT), total cholesterol and triglyceride were determined by routine laboratory methods. RESULTS: Compared to subjects with no family history of diabetes, the age and sex adjusted odds ratio (OR) of NAFLD was 1.83 (95% CI: 1.11-3.03) for FDR of patients with T2DM. After further adjusting for BMI, fasting glucose, ALT, asparate aminotransferase (AST), triglyceride and cholesterol, the multivariate OR of prevalent NAFLD in FDR of patients with T2DM compared with individuals with no family history of diabetes was 1.56 (95% CI: 0.85-2.86). CONCLUSIONS: The present study suggests that the relation between FDR of patients with T2DM and NAFLD is affected by the other covariates, in particular obesity, which points to a more complex relationship between the diseases. It appears that obesity and diabetes may independently predispose to NAFLD.